1975
DOI: 10.1103/physrevc.11.282
|View full text |Cite
|
Sign up to set email alerts
|

Coulomb excitation ofTe125

Abstract: The properties of the low-lying levels of '"Te were investigated by the Coulomb excitation process which was effected by bombarding a thick natural tellurium target with 9,5and 10.5-MeV 0. particles and a thick target of isotopically enriched '"Te (95%%uo) with 45-MeV ' 0 ions. Levels at 443.58, 463.39, 671.42, and 729.30 MeV were Coulomb excited and the reduced upward transition probabilities 8(E2t') (e'b) extracted from the. data were: 0.186 + 0.005, 0.158 + 0.005, 0.130 + 0.004, and 0.0059~0.0008. Angula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
237
1

Year Published

1979
1979
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(249 citation statements)
references
References 17 publications
11
237
1
Order By: Relevance
“…Assuming that the ratio of neutrons to protons is unity, B A is then calculated by dividing the cluster yield at a given momentum P A by the A-th power of the proton yields at P A /A. Figure 5 compares the results for B 2 and B 3 at p t = 0 from our study (red filled circles in figure 5) to experimental data from the Bevalac [18], AGS [5,19], SPS [20,21], and RHIC [22][23][24]. One concludes from this compilation that the coalescence parameters decrease only slowly with √ s NN over a broad range of collision energies: within the SPS energy range the variation of the coalescence parameter is less than 40% and 60% for B 2 and B 3 , respectively.…”
Section: Resultsmentioning
confidence: 87%
“…Assuming that the ratio of neutrons to protons is unity, B A is then calculated by dividing the cluster yield at a given momentum P A by the A-th power of the proton yields at P A /A. Figure 5 compares the results for B 2 and B 3 at p t = 0 from our study (red filled circles in figure 5) to experimental data from the Bevalac [18], AGS [5,19], SPS [20,21], and RHIC [22][23][24]. One concludes from this compilation that the coalescence parameters decrease only slowly with √ s NN over a broad range of collision energies: within the SPS energy range the variation of the coalescence parameter is less than 40% and 60% for B 2 and B 3 , respectively.…”
Section: Resultsmentioning
confidence: 87%
“…Hydrodynamical model is one of the established models for describing global features in the relativistic nuclear collisions as collective flow. Recently, anisotropic flow phenomena have been observed at AGS [2,3] and also at SPS [4,5,6]. Several authors have argued the relation between the behavior of the collective flow and the equation of states.…”
Section: Introductionmentioning
confidence: 99%
“…Since Danielewicz showed that elliptic flow is sensitive on nuclear equation of state in AGS energy [8], the elliptic flow is one of the hottest topics in high energy nuclear physics. The high accuracy experiments for elliptic flow have been done at AGS [2,3] and SPS [4,5,6]. Recently, using the cascade model of the ART, Li discussed the elliptic flow in the deformed uranium collisions.…”
Section: Effect Of Deformed Uranium On Collective Flowmentioning
confidence: 99%
“…The solid lines are our results, the ones dashed are the results with isochronous freeze-out from [18] (b, c). Experimental points for E lab = 6 AGeV are taken from [20], for E lab = 10.7 AGeV - [21] (triangles), [22] (squares) and [23] (circles), and for E lab = 40 AGeV - [24] (squares) and [25] (the circle).…”
Section: The Two-stage Versionmentioning
confidence: 99%